PEDAGOGICAL CONDITIONS FOR FORMING CROSS-DISCIPLINARY COMPETENCE IN FUTURE TEACHERS OF VOCATIONAL TRAINING - Prylepa Ivan (Alfred Nobel University Publisher, 2023)
It has been established that the ongoing process of European integration in our country requires the creation of a competitive educational system, which mainly depends on the scientific and creative potential and innovative activities of educators. From this point of view, the reform of the national system of professional education at this stage involves a significant expansion of the content areas of the professional activity of pedagogical staff of educational institutions at all levels. In particular, there is a task of forming cross-disciplinary competence in vocational education teachers, since they are responsible for the high-quality training of eminently qualified specialists for the current labour market. The purpose of the article is to highlight the pedagogical conditions for forming cross-disciplinary competence in future teachers of vocational training. The task of the study is to identify and characterize the pedagogical conditions for the development of cross-disciplinary competence in future teachers of vocational training. In the study, the following research methods have been used: analysis and synthesis, comparison, summarization of primary sources, expert evaluation and survey of scientific and pedagogical staff regarding the definition of the list of pedagogical conditions for forming cross-disciplinary competence in future teachers of vocation training The article analyses the pedagogical conditions that contribute to the implementation of current trends in reforming educational systems and comprehensive personality development in terms of higher education institutions. In the study, the pedagogical conditions are considered as a factor or driving force for improving the quality of the learning process. Pedagogical conditions usually combine the performing of pedagogical actions with the use of appropriate forms and methods, and the results of students' educational activities. At the same time, pedagogical conditions are a set of objective possibilities, content, methods, organizational forms, and material means for the realization of the pedagogical process; they reflect the basic requirements for the organization of pedagogical activity, and ensure the successful achievement of the set goal. It has been noted that pedagogical conditions can be classified into organizational and pedagogical, methodical, social and psychological, material and technical and aesthetic ones. Pedagogical conditions appropriate for forming cross-disciplinary competence among future teachers of vocational training have been singled out, namely: motivation of future teachers of vocational training to master cross-disciplinary competence; cross-disciplinary integration of students' theoretical and practical training for the development of their cross-disciplinary competence; training of scientific and pedagogical staff to implement a cross-disciplinary approach in the educational process; implementation of the methods for forming cross-disciplinary competence in future teachers of vocational training. In order to identify the pedagogical conditions that will ensure forming cross-disciplinary competence in future teachers of vocational training, their needs in possessing pedagogical and technical knowledge have been primarily taken into account. Special attention is paid to the use of cross-disciplinary connections in higher education institutions which is a guarantee for forming cross-disciplinary competence in future specialists. Based on the results of the study, it has been concluded that modern teachers of vocation training should possess hard skills and soft skills, and be able to quickly find cause-and-effect relationships to solve various situations which are formed and improved within the limits of their cross-disciplinary competence.